FEATURES OF TEACHING OPHTHALMOLOGY BASED ON CLINICAL CASES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the pedagogical and methodological features of teaching ophthalmology based on clinical cases in modern medical education. The integration of clinical case-based learning (CBL) into ophthalmology enhances students’ diagnostic competence, critical thinking, and decision-making abilities. The study highlights the importance of reflective learning, simulation-based environments, and problem-oriented discussions in fostering clinical reasoning skills.